Lexical Access in the Production of Spoken Language from the Perspective of Neurolinguistics - bechiri, ammar (El Omda in Linguistics and Discourse Analysis, 2025)
This study aims to highlight the aspect of lexical access and its role in language production from a neurolinguistics point of view, based theories, such as Levelt and his team and Dahl and his team, and their approach to this process, as well as balanced processing, and discussing some models and their interactions that have contributed to the explanation of language production and errors that occur in normal people and in pathological cases.